Factors contributing to economic burden in lung cancer spousal caregivers. Issue 3 (14th May 2014) - Kavanaugh, Melinda; Kramer, Betty J.; Walsh, Matthew Cunningham; Trentham-Dietz, Amy
Abstract: Objective: The determinates of economic burden in lung cancer caregivers are poorly understood. Of particular interest is the role patient symptoms play in caregiver economic burden. Guided by a stress process conceptual framework, this study examined the predictors of economic burden reported by lung cancer spousal caregivers. Our study focused on the pathway of contextual and stressor variables leading to economic burden in lung cancer caregivers. Method: Relying on survey data from 138 spouses, structural equation modeling was employed to examine the determinants of economic burden measured using the Family Impact Survey. Contextual variables included age, gender, education, and income; and stressor variables included patient physical and mental symptoms, as well as number of children in the home. Results: A significant indirect path between age and economic distress through patient symptoms ( p = 0.05) indicates younger spouses providing care for patients with more symptoms and reporting greater economic burden. Direct effects between contextual variables and economic burden revealed that caregivers with less education ( p = 0.02) and those with more children at home ( p = 0.01) reported more adverse economic outcomes. Significance of Results: Numerous factors impact spousal caregivers' economic burden, including the presence of children at home, being a younger caregiver, and lower educational attainment by caregivers. Moreover, the direct effects between age and economic burden were not significant, supporting the clear role patient symptoms play in the path to economic burden in spousal caregivers. These results underscore the need for healthcare providers to address psychosocial factors when dealing with patients and families with lung cancer. Specifically, the results highlight the importance of addressing patient symptoms early before they threaten the family's economic well-being.